ANALYZING THE USE OF QUIZIZZ IN VOCABULARY DEVELOPMENT FOR JUNIOR HIGH SCHOOL STUDENTS - Tata Regita Sherfaty Irawan; Masagus Firdaus (Al-Irsyad: Journal of Education Science, 2025)
This study aims to analyse the use of the online learning platform Quizizz in the vocabulary development of junior high school students. The primary focus is to evaluate the effectiveness of Quizizz as a learning tool in enhancing English vocabulary mastery. A quantitative approach was employed using a quasi-experimental design involving two groups of students: an experimental group using Quizizz and a control group using traditional methods. The results indicate that students who used Quizizz showed a significant improvement in vocabulary acquisition compared to those in the control group. These findings suggest that the use of Quizizz not only increases student engagement but also positively impacts their academic achievement in vocabulary learning. The study recommends integrating Quizizz as part of vocabulary teaching strategies in junior high schools.This study aims to analyse the use of the online learning platform Quizizz in the vocabulary development of junior high school students. The primary focus is to evaluate the effectiveness of Quizizz as a learning tool in enhancing English vocabulary mastery. A quantitative approach was employed using a quasi-experimental design involving two groups of students: an experimental group using Quizizz and a control group using traditional methods. The results indicate that students who used Quizizz showed a significant improvement in vocabulary acquisition compared to those in the control group. These findings suggest that the use of Quizizz not only increases student engagement but also positively impacts their academic achievement in vocabulary learning. The study recommends integrating Quizizz as part of vocabulary teaching strategies in junior high schools.